ANALISIS MANAJEMEN PEMBELAJARAN BERBASIS STEM UNTUK MENGHADAPI ERA 5.0 SOCIETY - Agus Sugiarto; Rahmat Mulyono (STKIP Subang, 2022)
Changes in the era of society 5.0 cannot be avoided. The rapid change of times has made all aspects of life also required to experience changes as well as society. The purpose of this research is to analyze STEM-based learning management in order to prepare for changes in the era of society 5.0 which is a qualitative research with a library research approach. The era of society 5.0 is the era of super smart society where humans are required to be able to live side by side with technology, all activities in aspects of life are influenced by technology which aims to make humans live more effectively and comfortably. Education is one of the agents in preparing the younger generation to compete in this era of change. Therefore, STEM is an approach that is able to provide preparation for students in facing the era of society 5.0, because STEM is one of the characteristics of learning that teaches and trains 21st century skills needed in the era of society 5.0. As for STEM-based learning management, there needs to be careful preparation for both teachers and students so that learning can run optimally. In its implementation, the teacher's perspective on STEM is positive, but there are still many challenges that must be faced, one of which is related to the teacher's preparation of learning and the use of technology in learning As for STEM-based learning management, there needs to be careful preparation for both teachers and students so that learning can run optimally. In its implementation, the teacher's perspective on STEM is positive, but there are still many challenges that must be faced, one of which is related to the teacher's preparation of learning and the use of technology in learning As for STEM-based learning management, there needs to be careful preparation for both teachers and students so that learning can run optimally. In its implementation, the teacher's perspective on STEM is positive, but there are still many challenges that must be faced, one of which is related to the teacher's preparation of learning and the use of technology in learning.